The Comparison of the Kidney Effects of Dipeptidyl Peptidase 4 Inhibitors and Glucagon-Like Peptide 1 Agonist-Administered Concomitant with Sodium-Glucose Cotransporter 2 Inhibitors in Japanese Patients with Type 2 Diabetes Mellitus and Chronic Kidney Disease - Kazuo Kobayashi; Masao Toyoda; Nobuo Hatori; Kazuyoshi Sato; Masaaki Miyakawa; Kouichi Tamura; Akira Kanamori (Journal of Diabetes Research)
Background and Aim. Strong evidence exists supporting the utility of sodium glucose cotransporter inhibitors (SGLT2is) for treating not only cardiovascular events but also renal events. We previously reported that SGLT2is improved the urine albumin-to-creatine ratio (ACR) in Japanese patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD). Only 8% of patients were treated with SGLT2is alone, and more than 70% of them additionally received incretin-related agents, such as dipeptidyl peptidase 4 inhibitor (DPP4i) and glucagon-like peptide 1 agonist (GLP1Ra). Both agents reduce the plasma glucose level with an incretin effect, but the differences in the renoprotective effects between these agents are poorly understood. Methods. We retrospectively constructed database of 763 Japanese patients with T2DM and CKD who received sSGLT2is for more than 1 year. Among these SGLT2i-treated patients, 338 were receiving concomitant DPP4i (DPP4i group), and 99 were receiving concomitant GLP1Ra (GLP1Ra group). The two groups were compared using the propensity score matching method. Results. In the matched model including 86 cases per group, the decrease in the logarithmic value of the ACR and rate of reduction in the estimated glomerular filtration rate (eGFR; mL/min/1.73 m2) of the GLP1Ra group showed no significant difference from those in the DPP4i group (−0.12±0.48 vs. −0.13±0.45 and −2.3±18.5 vs. −6.2±13.8, respectively, P=0.10). However, the incidence of a >6.4% decrease in the eGFR was significantly lower in the GLP1Ra group than in the DPP4i group (35% vs. 52%, respectively, P=0.03). The level of hemoglobin A1c (mmol/mol) after SGLT2i treatment was significantly lower in the DPP4i group than in the GLP1Ra group in the matched model (58.3±11.8 and 62.7±14.8, respectively, P=0.02). Conclusion. Among the SGLT2i-treated patients with T2DM and CKD, concomitant treatment with GLP1Ra has a marked improving effect on the change in the eGFR.